Special Issue "Nonsmooth Optimization in Honor of the 60th Birthday of Adil M. Bagirov": Foreword by Guest Editors - Napsu Karmitsa; Sona Taheri (MDPI, 2022)
Nonsmooth optimization refers to the general problem of minimizing (or maximizing) functions that have discontinuous gradients. This Special Issue contains six research articles that collect together the most recent techniques and applications in the area of nonsmooth optimization. These include novel techniques utilizing some decomposable structures in nonsmooth problems-for instance, the difference-of-convex (DC) structure-and interesting important practical problems, like multiple instance learning, hydrothermal unit-commitment problem, and scheduling the disposal of nuclear waste.